Geochemical background and threshold for 47 chemical elements in Slovenian topsoil - Gosar, Mateja; Šajn, Robert; Bavec, Špela; Gaberšek, Martin; Pezdir, Valentina; Miler, Miloš (Geologija, 2019)
Geochemical background and threshold values need to be established to identify areas with unusually high concentrations of elements. High concentrations are caused by natural or anthropogenic processes. The <2 mm fraction of 817 collected topsoil (0 – 10 cm) samples at a 5 × 5 km grid on the territory of Slovenia was analysed. Results are used here to establish the geochemical background variation and threshold values, derived statistically from the data set, in order to identify unusually high element concentrations for these elements in the soil samples. Geochemical threshold values were determined following different methods of calculation for (1) whole of Slovenia and (2) for 8 spatial units determined on the base of geological structure, lithology, relief, climate and vegetation. Medians and geochemical thresholds for whole of Slovenia were compared with data for Europe and for southern Europe separately, since large differences in the spatial distribution of many elements are observed between northern and southern Europe. Potentially toxic elements (PTEs), namely As, Cd, Co, Cr, Cu, Hg, Mo, Ni, Pb, Sb, and Zn, are of particular interest. Medians of these PTE elements are all higher in Slovenia than in southern Europe. Medians of Pb and Mo are 1.5 times higher and medians of Hg and Cd are even more than 2 times higher in Slovenia. Geochemical thresholds for As, Cr, Co, Ni, Sb and Zn are of similar values in both Slovenia and southern Europe and some lower for Cu and Ni. Up to 1.5 times higher are tresholds in Slovenia for Mo and Pb and more than 2.5 times higher for Cd and Hg. These values were then compared to existing Slovenian soil guideline values for these elements.